Diseño de un controlador avanzado para el control de nivel en el sistema de tanques interconectados del Laboratorio de Automatización de la CIEM - Romero Jara, Roger Javier (2023)
The present degree project approaches the design and evaluation through the simulation of a predictive controller based on model (MPC) to control the level in the tank system interconnected from Automation Laboratory of Electromechanics Engineering career, with the purpose to compare the characteristics that presents an advanced level controller system regarding PID conventional control and quantify its development, because this last results being inefficient when the process is complex and presents large time delays. It started by obtaining the mathematical model that describe the dynamic behavior of study plant, through the system identification method, using the tool that provides MATLAB® for this process. Then, it was tunning the predictive controller using an evolutive algorithm with an objective function set for this case, in order to determine which parameters allows to get an optimal controller; using the MPC Toolbox of MATLAB®. At the same time, also it was designed a PID control for the interconnected systems tanks, considering the physics limitations of the actuator through a strategy known as anti-windup, improving the control answer. Setting up both controllers in Simulink their performance was evaluated through simulation and it was quantifier their outcomes, where it is evinced that the predictive controller presents a better performance compared to classic PID controller. In addition, it was developed an application through a GUI platform which allows to the user select each one of brought case and run the simulation of the plant with the MPC and PID controllers designed, being able to observe through graphics their behavior and performance; therefore, it has the option of modify each one of the parameters preestablish MPC, thus it can make a manual tunning and run their simulation to compare results. Key words: level control, MPC, PID controller, anti-windup, time delays, systems identification.